Modulation of Hybrid GRM2-type Bacterial Microcompartment Shells through BMC-H Shell Protein Fusion and Incorporation of Non-native BMC-T Shell Proteins - Česle, Eva Emi Lija; Ta Rs, Kaspars; Jansons, Juris; Kalniņš, Gints (ACS synthetic biology, 2023)
Bacterial microcompartments (BMCs) are organelle-like structures in bacteria that facilitate a wide range of enzymatic reactions. The microcompartment shell contains an encapsulated enzymatic core and, in contrast to phospholipid-based eukaryotic organelle membranes, has a pseudoicosahedral shape composed of BMC-H, BMC-T, and BMC-P proteins with conserved structures. This semipermeable microcompartment shell delineates the enzymatic core assemblies and the intermediates from the rest of the cell. It is also thought to function as a barrier against toxic intermediates as well as to increase the reaction rate. These properties of BMCs have made them intriguing candidates for biotechnological applications, for which it is important to explore the potential scope of the BMC shell modulation possibilities. In this work, we explore two BMC shell modulation mechanisms: first, confirming the incorporation of three trimeric BMC-T shell proteins and two truncated BMC-T shell proteins into Klebsiella pneumoniae GRM2-type BMC protein shells containing no representatives of this group, and second, producing BMC particles from double- and triple-fused hexameric BMC-H shell proteins. These results reveal the potential for "mix and match" synthetic BMC shell formation to ensure shell properties specifically suited to the encapsulated cargo and show for the first time the involvement of an essentially dimeric pseudohexameric shell protein in BMC shell formation.Bacterial microcompartments (BMCs) are organelle-like structures in bacteria that facilitate a wide range of enzymatic reactions. The microcompartment shell contains an encapsulated enzymatic core and, in contrast to phospholipid-based eukaryotic organelle membranes, has a pseudoicosahedral shape composed of BMC-H, BMC-T, and BMC-P proteins with conserved structures. This semipermeable microcompartment shell delineates the enzymatic core assemblies and the intermediates from the rest of the cell. It is also thought to function as a barrier against toxic intermediates as well as to increase the reaction rate. These properties of BMCs have made them intriguing candidates for biotechnological applications, for which it is important to explore the potential scope of the BMC shell modulation possibilities. In this work, we explore two BMC shell modulation mechanisms: first, confirming the incorporation of three trimeric BMC-T shell proteins and two truncated BMC-T shell proteins into Klebsiella pneumoniae GRM2-type BMC protein shells containing no representatives of this group, and second, producing BMC particles from double- and triple-fused hexameric BMC-H shell proteins. These results reveal the potential for "mix and match" synthetic BMC shell formation to ensure shell properties specifically suited to the encapsulated cargo and show for the first time the involvement of an essentially dimeric pseudohexameric shell protein in BMC shell formation.